Cerebrospinal fluid NFL in the differential diagnosis of parkinsonian disorders: A meta-analysis. (15th October 2018) - Ge, Fangfang; Ding, Jiaqi; Liu, Yu; Lin, Hong; Chang, Ting
Highlights: The CSF NFL levels in APD were significantly elevated relative to PD and healthy controls. The CSF NFL levels can differentiate APD from PD with high sensitivity, specificity and diagnostic accuracy. Prospective study design, and duration and severity of the disease may affect test performance. Large and longitudinal studies are still needed on individuals who are suspected to have APD. Abstract: Neurofilament light chain (NFL) in cerebrospinal fluid (CSF) is a promising biomarker candidate which may discriminate atypical parkinsonian disorders (APD), mainly including multiple system atrophy (MSA), progressive supranuclear palsy (PSP), and corticobasal degeneration (CBD), from Parkinson's disease (PD). We aim to evaluate the diagnostic accuracy of CSF NFL level as a differentiating biomarker between APD and PD. Databases of PubMed, OVID and Web of Science were searched for studies (published until May 31, 2017) that reported on CSF NFL as a diagnostic biomarker between APD and PD. Eight studies were pooled in this meta-analysis, including 341 PD and 396 APD patients and 388 healthy controls. The pooled sensitivity was 82% (95% CI, 68%–91%) and specificity was 85% (95% CI, 79%–89%) in differentiating APD from PD. The pooled positive likelihood ratio (PLR), negative likelihood ratio (NLR) and diagnostic odds ratio (DOR) were 5.4 (95% CI, 3.6%–8.1%), 0.21 (95% CI, 0.11%–0.40%), and 25 (95% CI, 9%–69%) respectively; and the area under the curve (AUC) was 0.89 (95% CI, 0.86%-0.91%). Subgroup analysis revealed sensitivity and specificity were significantly influenced by study design. The APD subtypes, disease duration and severity were the main heterogeneity sources in specificity. The results of Deeks' test revealed a low risk of publication bias. The CSF NFL level may be used as a biomarker in discriminating APD from PD with high diagnostic accuracy at an early stage of disease. Large and longitudinal studies are still needed on individuals who are suspected to have APD.